Pengaruh Kualitas Pelayanan dan Keragaman Produk Tabungan terhadap Minat Menabung Masyarakat Bondowoso pada Bank Muamalat - Wafa, Mochammad Ali; Lilis Yuliati; Agung Budi Sulistiyo (IJABAH, 2023)
The aim of this research is to find and examine the relationship between service quality and the diversity of savings products in attracting Bondowoso people's interest in saving at Bank Muamalat. Quantitative research is the type now used. The Bondowoso community was the target of this research, which included a sample of 100 respondents from each of the five sub-districts of Sukosari, Tapen, Wonosari, Tenggarang and Bondowoso. Multiple linear regression is the analysis tool used. The following are the findings from the multiple linear regression analysis coefficient assessment: 1) With a beta test coefficient of 0.249, service quality has a good and significant effect on the Bondowoso people's desire to save at Muamalat Bank; 2) With a beta test coefficient of 0.446, the diversity of savings products has a good and significant effect on the Bondowoso people's desire to save at Bank Muamalat; 3) With the beta test coefficient, service quality and diversity of savings products have a good and significant effect on the Bondowoso people's desire to save at Bank Muamalat.